Comparative study of larvicidal activity of commercial essential oils from aromatic rosemary, vanilla, and spearmint against the mosquito Aedes aegypti - SEDTHAPONG LAOJUN; Tanawat Chaiphongpachara (Society for Indonesian Biodiversity, 2020)
Abstract. Laojun S, Chaiphongpachara T. 2020. Comparative study of larvicidal activity of commercial essential oils from aromatic rosemary, vanilla, and spearmint against the mosquito Aedes aegypti. Biodiversitas 21: 2383-2389. Dengue fever is a dangerous mosquito-borne viral disease of humans. This disease is caused by dengue virus, a member of the genus Flavivirus of the family Flaviviridae. The Aedes aegypti mosquito is a principal vector for this virus. To control Ae. aegypti populations, there is extensive focus on larval eradication, because breeding sites are often close to human populations, especially man-made containers. The objective of this research was to evaluate the efficacy of commercial essential oils from rosemary (Rosmarinus officinalis), vanilla (Vanilla planifolia), and spearmint (Mentha spicata) with regard to larvicidal activity against Ae. aegypti larvae after 24 and 48-hours of exposure in the laboratory. The results showed highly efficacious larvicidal activity, with median lethal doses (LC50) of 0.23, 0.10, and 0.12 ppm after 24-hour exposure to commercial rosemary, vanilla, and spearmint oil, respectively. The results of this study will be useful for the control of a common dengue vector and may replace the use of pesticides that may have broad environmental impacts.